A novel 3300 V trench IGBT with P-N-doped polysilicon split gate for low EMI noise. (1st April 2022) - Wang, Tongyang; Li, Zehong; Zhao, Yishang; Li, Luping; Yang, Yang; Xia, Ziming; Ren, Min; Li, Wei; Zhang, Jinping
Abstract: A novel 3300 V trench insulated gate bipolar transistor (IGBT) with p-n-doped polysilicon split gate (PNSG-IGBT) is proposed for low electromagnetic interference noise. The reverse-biased polysilicon PN junction is laterally depleted and charged by displacement current during the turn-off transient, which raises electrostatic potential in n-region of the polysilicon PN junction ( V N ) and electrostatic potential under the gate oxide ( V ACC ) simultaneously. By technology computer aided design simulation, during the turn-on transient, the maximum d V ACC / d t is 57.1% lower than that of the split gate (SG)-IGBT with the same R G and the excess V GE overshoot caused by reverse displacement current is effectively suppressed. Moreover, for the same E ON, the maximum reverse recovery d V KA / d t of the freewheeling diode can be reduced by 77.3% and 30.7% compared with that of the floating P region-IGBT and the SG-IGBT respectively, which is of great merit in suppressing d V/ d t noise. Consequently, the PNSG-IGBT shows less common-mode noise at high frequency, especially in the range of 20–40 MHz.